The inhibition of apoptosis through myocardial postconditioning by affecting Fas/FasIg signaling through miR139-3p and miR181a-1 - Aslan, Gulnur; Atessahin, Ahmet; Sahna, Engin (Wiley, 2020)
Background and Aim of the study Ischemic postconditioning (PostC) is considered to be one of the strongest mechanisms limiting the extent of myocardial infarction, and reducing ischemia-reperfusion (I/R) injury. I/R-induced myocardial injury results in apoptosis, autophagy, and necrosis. The aim of the present study was to investigate the roles of the necrotic gene cytochrome b-245 beta chain (Cybb); Cybb-related microRNA miR139-3p; the autophagy gene Beclin-1 (Becn1); proapoptotic genes Fas, Faslg and growth arrest and DNA-damage-inducible 45 alpha (Gadd45a); and apoptosis-related microRNA miR181a-1 levels on I/R injury, as well as, the potential protective effects of PostC through this gene and microRNAs. Methods The left main coronary artery was subjected to ischemia for 30 minutes, followed by reperfusion for 120 minutes. PostC involved three cycles of I/R, each lasting 10 seconds. Gene and microRNA levels were analyzed using a quantitative reverse transcription-polymerase chain reaction. Results Although an increase was observed in the expression levels of the Cybb, Fas, Faslg and Gadd45a genes, the miR139-3p, miR181a-1, and Becn1 expression levels were found to decrease with I/R injury. PostC was determined to restore the expression of all the genes to the normal levels. Conclusions The abovementioned genes can be used as important prognostic markers in the diagnosis of reperfusion injury and in the evaluation of treatment efficacy. It was further noted that increased expression of CYBB, which is one of the target genes for miR139-3p, and a decreased expression of miR181a-1 may cause apoptosis by affecting Fas and Faslg signaling. PostC can inhibit apoptosis by increasing miR139-3p and miR181a-1 levels.
Keywords: Becn1; Fas; ischemic postconditioning; miR139-3p; miR181a-1; Nox2